Implementasi Kurikulum Merdeka Belajar Dalam Pandangan Filsafat Idealisme - Salmiyanti Salmiyanti; Desyandri Desyandri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The prescriptive philosophical foundation of education will provide clues about what should be aspired to in education. Education is not enough to be understood only with a descriptive scientific approach, but must also be understood holistically. The purpose of this research is about the implementation of the independent learning curriculum in the view of the philosophy of idealism. The method used is a literature study. This literature review is a study in the form of books, articles, references relating to the ideals of education in Indonesia which can be used as references in the implementation of similar studies. Similar research was also conducted to obtain valid and accurate conclusions. The relationship between philosophical idealism and independent learning is a unity that cannot be separated. The concept of independent learning is part of efforts to create a primary and secondary education system. With this concept, a specific strategy is chosen to issue various things in implementation. Educators' understanding of philosophy as the basis of knowledge is very important as a basis for reflection and as a basis for implementing the concept of independent learning which is carefully structured for the purposes of reforming the education system in Indonesia.